An Adaptable High-Throughput Technology Enabling the Identification of Specific Transcription Modulators. (April 2017) - Bergbrede, Tim; Hoberg, Emily; Larsson, Nils-Göran; Falkenberg, Maria; Gustafsson, Claes M.
Mitochondria harbor the oxidative phosphorylation (OXPHOS) system, which under aerobic conditions produces the bulk of cellular adenosine triphosphate (ATP). The mitochondrial genome encodes key components of the OXPHOS system, and it is transcribed by the mitochondrial RNA polymerase, POLRMT. The levels of mitochondrial transcription correlate with the respiratory activity of the cell. Therefore, compounds that can increase or decrease mitochondrial gene transcription may be useful for fine-tuning metabolism and could be used to treat metabolic diseases or certain forms of cancer. We here report the establishment of a novel high-throughput assay technology that has allowed us to screen a library of 430, 000 diverse compounds for effects on mitochondrial transcription in vitro. Following secondary screens facilitated by the same assay principle, we identified 55 compounds that efficiently and selectively inhibit mitochondrial transcription and that are active also in cell culture. Our method is easily adaptable to other RNA or DNA polymerases and varying spectroscopic detection technologies.